Implementation of Health Promoting School in Efforts to Prevent Covid-19 at the Kenjeran Village Elementary School, Surabaya City - Riris Diana Rachmayanti; Annis Catur; Fariani Syahrul (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
The Covid-19 pandemic still hasn't subsided. On October 22, 2020 in Surabaya, there were 15,530 confirmed cases, 161 confirmed cases of treatment, 14,226 confirmed cases of recovery, and 1,143 confirmed deaths. In Surabaya, Covid-19 cases spread evenly in all sub-districts. The purpose of this activity was increased the knowledge of elementary school students about the prevention of Covid-19. In this activity, one group pre-test and post-test was used. The sample was 4th grade and 5th grade elementary school students in total 109 children in Kenjeran District, Surabaya City. Interventions were pocket books and videos. The result of this activity was increased students' knowledge before and after the intervention. After knowledge intervention in the less than 13.6% category, it fell to 1.5%. Knowledge in the good category increased from 7.3% to 15.5% and knowledge in the very good category increased from 73.6% to 76.4%. The conclusion of this activity was that the media used in the health promotion school is very effective in increasing students' knowledge as evidenced by the knowledge increasement that occured before and after the intervention, the average knowledge increasement was 10% in each category.